TINJAUAN ATAS PENGUKURAN NILAI PERUSAHAAN DENGAN METODE TOBIN’S Q TAHUN 2018-2021 PADA PT KIMIA FARMA TBK - Putra, Candra Basroni; Komarudin, Mochamad Fahru (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2026)
PT Kimia Farma Tbk's firm value from 2018 to 2021 will be calculated by considering the company's asset management. The research strategy employed in this work is a quantitative descriptive approach. The Tobin's Q approach was employed for data analysis in this study. In 2018, the firm's value was Q>1, indicating that asset management was successful and the stock was overvalued, according to the results for PT Kimia Farma Tbk. On the other hand, the firm's valuation was Q1 in 2019, which indicates that the stock was overvalued and that asset management was successful. Among the years 2018–2021, the year with the highest firm value according to Tobin’s Q was 2018.